Optical laser-generated electricity for powering tilt-meter sensor - Nelfyenny, Nelfyenny; Bayuwati, Dwi; Suryadi, Suryadi; Husdi, Irwan Rawal; Mulyanto, Imam; Prasetio, Aditya Dwi; Irawan, Dedi; Widiyatmoko, Bambang; Setiono, Andi (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This research investigated the feasibility and efficacy of power over fiber (PoF) transmission systems for geotechnical monitoring applications, addressing challenges associated with traditional power transmission methods. Leveraging fiber optic technology, PoF systems offer advantages such as high reliability, minimal signal loss, and immunity to environmental factors. The study presents a detailed design and implementation of a PoF transmission system, integrating a high-power laser source (HPLS) and photovoltaic technology for efficient power transmission over extended distances. Results demonstrate impressive volt-ampere characteristics and conversion efficiencies, with the optimized system configuration achieving a peak power output of 682 mW. Furthermore, the study evaluated the performance of a surface inclinometer sensor powered by the PoF system, showcasing its effectiveness in monitoring soil movements with remarkable stability and consistent power supply. Future research directions include scalability studies, optimization of system efficiency, and field deployments to broaden the applicability of PoF technology in geotechnical monitoring, ultimately advancing disaster mitigation and infrastructure resilience efforts.